Ion channel function of polycystin-2/polycystin-1 heteromer revealed by structure-guided mutagenesis - Staudner, Tobias; Khamseekaew, Juthamas; Madej, M. Gregor; Geiges, Linda; Azemi, Bardha; Ziegler, Christine; Korbmacher, Christoph; Ilyaskin, Alexandr (Febs Letters, 2025)
Mutations in polycystin-1 (PC1) or polycystin-2 (PC2) cause autosomal-dominant polycystic kidney disease (ADPKD). Structural data suggest that one PC1 and three PC2 form heterotetrameric ion channels with an ion permeation pathway blocked by PC1 (R4100, R4107, and H4111) and PC2 (L677, N681) residues. Here, we demonstrate that replacing these residues with alanines results in a gain-of-function (GOF) PC2/PC1 construct with distinct selectivity properties compared to PC2 homomers. We also show preferential formation of PC2/PC1 heteromeric complexes over PC2 homomers. Re-interpretation of published PC2/PC1 cryo-electron microscopy data, combined with cysteine modification experiments, suggests that the pore-forming domain of PC1 adopts a canonical TRP channel-like conformation. This novel PC2/PC1 GOF construct offers the opportunity to investigate the functional impact of ADPKD mutations.
CRIS-Team Scopus Importer:2025-05-23
Keywords: ADPKD; electrophysiology; polycystin-1; polycystin-2; TRP channels